Progress and challenges in consolidating the management of Amazonian protected areas and indigenous territories - Gullison, Raymond E (Conservation biology : the journal of the Society for Conservation Biology, 2018)
© 2018 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.